Effects of drop height, conveyor belt speed, and acceleration on the welfare of broiler chickens in early and later life - Mona F. Giersberg (Poultry Science, 2020)
During automated processing in commercial hatcheries, day-old chicks are subjected to a range of possible mental and physical stressors. Three determinants of the processing line seem to have the potential to affect the birds in particular: drop height from one conveyor belt to another, conveyor belt speed, and acceleration. The aim of this study was to evaluate the effects of these 3 factors on chicken health and welfare in early and later life. In a first trial, chickens were tested on an experimental processing line that was adjusted to different levels of drop heights, belt speeds, and accelerations separately (n = 14 animals per factor and increment). Besides the assessment of several indicators for disorientation during the treatment, postmortem radiographic images were created and analyzed with focus on traumatic injuries. The number of chickens changing their orientation after the drop was affected by drop height (P < 0.01), whereas body posture changes were affected both by drop height (P < 0.01) and belt speed (P < 0.01). Traumatic injuries were found only sporadically and were not related to a certain treatment. In a second trial, chickens that were exposed to a combination of the 3 processing factors were compared with an untreated control group (n = 63 per group) until 15 d of age. There were no differences between the 2 groups regarding BW, welfare scores, and fear-related responses in a novel object and in a tonic immobility test. The present results suggest that the treatments on the experimental conveyor belts affected the birds' health, welfare, and behavior to a limited extend. However, starting at a drop height of 280 mm and a conveyor belt speed of 27 m/min, significantly more chickens were not able to maintain their initial body position on the belt. This indicates that there may be scope for discomfort and welfare impairment if commercial systems are operated with considerably larger drop heights and at higher speeds.